Male aggressive behaviors as an indicator in primate tourism management assessment - Bin Yang; James R. Anderson; Meng-Ya Han; Xin-Yu Meng; Jun Luo; Kang-Sheng Jia; Yong-Feng Chen; Wen-Yong Tian; Bing-Bo Qiao; Chao Zhang; Han-Qing Jing; Pei-Yuan Zhou; et al. (Global Ecology and Conservation, 2024)
Primate tourism brings many benefits, but also some problems. How to better evaluate primate tourism is of significance for formulating tourism management strategies. In this study, we compared the aggressive behavior of three Sichuan snub-nosed monkey groups that encounter ecotourists and found that male aggressive behavior is a useful indicator for assessing ecotourism of these and, by inference, other groups. In high-risk tourism groups multiple monkeys direct aggression towards tourists, whereas low-risk tourism groups are characterized by low rates of such aggression. We found that tourists touching or attempting to touch the monkeys can trigger aggressive behaviors in all groups, while carrying food and eating have different effects across groups. In well-managed groups, tourist-directed aggressive behaviors are milder than in less well-managed groups. We propose that male monkey aggressive behavior elicited by tourists’ behavior is a useful indicator in assessing primate tourism, and can help guide further improvements in tourism management.